PROFIL SEKOLAH MTS ITTIHADUL KHOIRIYAH DESA MUARO JAMBI BERBASIS WEB - Novriana, Shinta Amelia; Suana, Irma; -, Afrizal (LP2M Universitas Nurdin Hamzah, 2024)
The rapid development of information technology is currently encouraging various sectors, including education, to adopt digital-based systems to increase operational efficiency and effectiveness. The MTs (Madrasah Tsanawiyah Swasta) Information System is designed to optimize data and information management in the Madrasah Tsanawiyah environment, covering academic and administrative aspects. This system integrates various features that enable data management to distribute information quickly and accurately. Apart from that, this system also supports the decision-making process by providing comprehensive and real-time reports to school management. MTs Information System Development uses web technology based on PHP and MySQL, with a user- friendly interface and high accessibility. The implementation results show that this system is able to increase the work efficiency of administrative staff, minimize errors in data recording, and strengthen communication between schools and parents.